A robust human face detection algorithm based on skin color segmentation and edge detection - Sharifara, Ali (Asian Research Publishing Network, 2015)
Automatic face detection is one of the interesting and challenging tasks in the field of computer vision. Face detection is the first and main step in many applications, especially in surveillance systems. In the present paper, a hybrid method is proposed to detect human face under different lighting conditions and complex backgrounds of color images. The proposed method have used skin color segmentation methods as well as edge detection to detect face in color images. In addition, a template matching process is applied based on a linear transformation in order to detect face for the selected regions. Thus, the process can be helpful in reducing false selected regions, which have same color as face.